Histochemical study and spermatogenesis eventsin testis of adult camel Camelus dromedarius inAL-Muthanna province (The Review of Diabetic Studies, 2025)
Objective; This study aimed to explain the histological features and spermatogenesis events in testis of mature camel. Materials and method; fourteen testes from adult camel collected from AL-Muthanna abattoir. The testis consists of a mass of seminiferous tubules, surrounded by fibrous capsule called tunica albuginea; which composed of dense collagenous tissue. A trabecula, pass inward from the tunica albuginea to form a framework for support of the seminiferous tubules gives off several trabeculae into the interior of the testis. These trabeculae divide the testis into lobules. Each lobule contains many seminiferous tubules. This capsule is covered by a tunica serosa, the connective tissue of which blends with the tunica albuginea. The tunica albuginea is continuous with the loose collagenous tissue of the mediastinum testis. Tunica albuginea is also continuous with the testis into the lobule testis; seminiferous tubules and rete testis are surrounded by loose collagenous tissue; Sertoli cells are elongated cells with irregular outlines extending from the basement membrane to the lumen. Leydig cells occurred in the interstitial space between the seminiferous tubules. The seminiferous tubules are associated with a specialized type of myoid cell. These cells are located within the surrounding basal lamina. Spermatogonia undergo mitosis to produce A-spermatogonia, Intermediate spermatogonia and B spermatogonia. This cyclic mitotic division activate B spermatogonia to produce primary spermatocyte that pass through six different phases; preleptotene, leptotene, zygotene, pachytene, diplotene and diakinesis phases. The secondary spermatocyte enters the second meiotic division which gives rise to spermatids.  Differentiated by fourteen stages which lead to form sperm. We can conclude that the study has shown the Although some characteristics unique to camels were noted, spermatogenesis in camels was largely comparable to that of the majority of mammalian species. It was discovered that spermatogenesis occurred continuously all year long.